Creating the conditions for psychological safety and its impact on quality coach-athlete relationships. (March 2023) - Jowett, Sophia; Do Nascimento-Júnior, Jose Roberto Andrade; Zhao, Chen; Gosai, Jyoti
Abstract: In this study, we investigated the notion that giving voice to athletes is an important aspect to creating a psychologically safe environment which can then feed into maintaining good quality coach-athlete relationships where every athlete feels heard, valued, and connected. 379 athletes completed a multi-section questionnaire that assessed their (a) capacity to be open and manage conflict with their coaches, (b) perceptions of psychological safety within their team or group, and (c) perceptions of the coach-athlete relationship quality. Structural equation modelling revealed that openness and conflict management positively predicted psychological safety which, in turn, positively predicted coach-athlete relationship quality. Psychological safety was found to explain the association between athletes' communication (i.e., capacity to be open, honest and transparent as well as manage interpersonal conflict effectively) and coach-athlete relationship quality regardless of athletes' gender. These findings highlighted that if athletes have the capacity to have candid discussions and can navigate conflict with their coaches, then it is possible to feel psychologically safe and thus able to engage in risky interpersonal interactions (e.g., raise concerns, admit mistakes) within their group context without fear of intimidation and humiliation. Furthermore, it was revealed that such a psychologically safe group environment fostered athletes' trust and respect, as well as commitment and cooperation with their coach. The discussion provides links to theory, research and practice. Highlights: The capacity of athletes to freely communicate as well as manage conflict with their coaches are salient communication strategies that are associated with "psychologically safe" group environments and with quality coach-athlete relationships. Practically, athletes who can openly communicate with their coaches are more likely to feel safe to communicate with their peers leading to better coach-athlete relationships. Overall, athletes can feel psychologically safe in an inherently competitive group environment when coaches set the tone by giving athletes' voice.